2007
DOI: 10.1097/ico.0b013e31802b28df
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Transplantation in Severe Bacterial Keratitis

Abstract: Early AMT combined with topical corticosteroid in severe BK provides immediate pain relief and allows epithelial healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 30 publications
2
36
0
4
Order By: Relevance
“…Thus, it may be a good alternative to PKP in eyes requiring a corneal graft, especially in acute cases in which the graft rejection risk is high. 22 Gicquel et al 21 report the use of early AMT in combination with antibacterial and topical steroid treatment in the management of severe bacterial keratitis or corneal infectious ulceration. Amniotic membrane transplantation was effective in inducing pain relief and epithelial healing and in reducing inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, it may be a good alternative to PKP in eyes requiring a corneal graft, especially in acute cases in which the graft rejection risk is high. 22 Gicquel et al 21 report the use of early AMT in combination with antibacterial and topical steroid treatment in the management of severe bacterial keratitis or corneal infectious ulceration. Amniotic membrane transplantation was effective in inducing pain relief and epithelial healing and in reducing inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…20,21 Moreover, the AM can act as a long-term drug delivery system (''reservoir effect''), becoming soaked with antibiotic and steroid agents after the instillation of several eyedrops. 21 Based on this hypothesis, Kim et al 22 used an AM soaked with antiinfective agents before transplantation for the treatment of infectious ulcerative keratitis; they report successful outcomes, with complete ulcer healing and epithelial closure or decreased size of epithelial defects in all the treated cases and no recurrence of infection or superinfection of ulcerated lesions. Multilayer AMT has been effective in preventing corneal perforation in eyes in which the ulceration was deep into the corneal stroma, in promoting corneal healing, and in reducing progressive stromal melting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In intractable infections, either gluing or suturing AM to the affected area has been shown to induce a favourable response to ongoing treatment. The exact mechanism of action of AM is unknown, but it is believed that the AM acts as a reservoir of the instilled medication and concentrates drug delivery to the site of infection [38,39] ( fig. 16 d-f).…”
Section: Surgical Options For Infective Keratitismentioning
confidence: 99%
“…20 In a group of patients with various infectious ulcers, AM promoted wound healing, reduced inflammation, and improved visual acuity in those without scarring. 21 In a recent report of patients with severe bacterial keratitis, Gicquel et al 22 reported immediate pain relief and epithelial healing that they attributed to early AM transplantation combined with topical corticosteroids.…”
mentioning
confidence: 97%